1988
DOI: 10.1136/adc.63.7_spec_no.715
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of neonatal intensive care.

Abstract: SUMMARY A cohort of very low birthweight infants (<1500 g) born in 1979-81 from a geographically defined area was followed up, and a costing of the initial admission to the neonatal intensive care unit was made. A four point scale for the severity of disability was used and estimation of the costs of education and full time residential care was made and discounted at 5% over the appropriate period. During the three years a progressively increasing proportion of infants survived, and this was associated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A review of the NHS Economic Evaluation database [13] revealed one similar study. Pharoah et al [14] compared the provision of neonatal intensive care in very low birth weight infants (< 1500 g) vs special care with no neonatal intensive care in the UK in 1984 and estimated an incremental cost per QALY gained of £2990. This suggests that intensive care represents good value for money in neonates.…”
mentioning
confidence: 99%
“…A review of the NHS Economic Evaluation database [13] revealed one similar study. Pharoah et al [14] compared the provision of neonatal intensive care in very low birth weight infants (< 1500 g) vs special care with no neonatal intensive care in the UK in 1984 and estimated an incremental cost per QALY gained of £2990. This suggests that intensive care represents good value for money in neonates.…”
mentioning
confidence: 99%
“…Of the 52 studies, 21 were based on geographically defined cohorts of infants 28 29 31 33 35 39 41 42 48 50 60 61 63 64 66 6873. The remaining studies were largely based on hospital-specific or convenience samples and, consequently, were likely to have been prone to selection biases.…”
Section: Resultsmentioning
confidence: 99%
“…Others estimate costs over a further extended time horizon,44 48 51 6063 6870 72 73 though the studies with the longer follow-up periods showed that the majority of healthcare costs occurred during the first 12 months of life. A series of studies from a group based in Merseyside, England, reported on the costs associated with a population-based cohort of low birthweight infants (<2000 g) born between 1979 and 1981 6870.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average cost of care for the extremely low-birthweight in fant is double the amount of the cost for neo nates weighting between 1,000 and 1,500 g. So far, we have not been able to make an estimate of the cost-benefit of care. This has been done in other countries [11,12]. Boyle, in 1983, calculated that intensive care was economically beneficial for babies with a birthweight between 1,000 and 1,499 g [13].…”
Section: Costmentioning
confidence: 99%